Schaum's Outline of Theory and Problems of Feedback and Control Systems / Continuous (Analog) and Discrete (Digital): Second Edition - Distefano Joseph J; Stubberud Allen R; Williams Ivan J (Mcgraw Hill, Inc, 1990)
Each outline series includes basic theory, definitions, and hundreds of carefully solved problems and supplementary problems. Introduction, Control System Terminology, Differential Equations and Difference Equations and Linear Systems, The Laplace Transform and the z-Transform, Stability, Transfer Functions, Block Diagram Algebra and Transfer Functions of Systems, Signal Flow Graphs, System Sensitivity Measures and Classification of Feedback Systems, Analysis and Design of Feedback Control Systems: Objectives and Methods, Nyquist Analysis, Nyquist Design, Root-Locus Analysis, Root-Locus Design, Bode Analysis, Bode Design, Nichols Chart Analysis, Nichols Chart Design, Introduction to Nonlinear Control Systems, Introduction to Advanced Topics in Control Systems Analysis and Design, Appendixes, References and Bibliography, Index.